Energiewende and its implications for Germany's energy security - Artur Ogurek; Robert Krzemien\'; Radosław Kaminski (The Central European Review of Economics and Management (CEREM), 2019)
Aim: In the 21st century, energy security is one of the most important elements of contemporary politics and economy. The German turn in energy policy is the first attempt on a global scale to move away from nuclear energy to the use of renewable energy (RES -Renewable Energy Sources), albeit with a temporary increase in the use of conventional energy sources (in particular coal). The authors undertook to analyze the course of the German policy turn as well as new opportunities and threats to the stability of its energy system, notably electricity sector.~Design / Research methods: In order to analyze the course of the German turn in energy policy as comprehensively as possible, the authors recurred to various studies, often presenting divergent points of view on changes in the German energy industry in recent years. The research process was based on the analysis of the content of the materials subject to consideration.~Conclusions / findings: The analysis carried out shows that the efforts to increase the share of renewable energy will be continued in the near future, while limiting the role of traditional energy sources, with the exception of lignite. The policy will also directly lead to a continued importance of natural gas for the global economy. The changes taking place in the German energy balance to a certain extent limit the country's energy security. This is due to the fact that supplies from wind and solar power plants that are to become dominant in the German energy system are of high volatility and thus constitute a significant threat. Progress in generating energy from renewable sources is not accompanied by similar progress in its storage, and without such storage capacity renewable energy sources will never be stable.~Originality / value of the article: The doctrinal assumptions of Energiewende (German energy transition) are fully consistent with the assumptions of the European climate and energy policy, which is also very important from the point of view of Poland. However, attention should be paid to the fact that too rigorous approach to its implementation may - still for a long time - threaten the economy and energy security of Germany and of other European Union states.~Implications: The conducted analysis unambiguously indicates the direction of the energy policy turn in Germany and in other EU states, as well as a change in the way the energy security system operates. The example of Germany, a highly industrialized country seeking to actively participate in the fulfillment of the commitments regarding the international mechanisms designed to combat the climate change, in particular by the transition of its energy sector towards a near zero emission economy, may provide model solutions which could potentially be adopted in other countries.
Keywords: Q48; 330; energy security; conventional energy; renewable energy sources; sustainable development; energy transition